Different surgical techniques for the management of small aortic annulus in patients with rheumatic aortic stenosis - Raafat Naeem, Mina; Mosallam Eisa, Karam; Khairy El Haiesh, Mahmoud; Abdel Bary Ahmed, Mohamed (Journal of Neonatal Surgery, 2025)
Background: Rheumatic Heart Disease (RHD) may cause aortic valve stenosis and with small aortic annuli, using small aortic valve prothesis can lead to Prosthesis-Patient Mismatch (PPM). Aortic root enlargement (ARE) techniques, such as Nicks, Manouguian, and Konno–Rastan, allow for using larger prosthetic valves, improving hemodynamics and patient outcomes. Aim: To evaluate surgical techniques for managing small aortic annuli in rheumatic aortic stenosis